Carbon Use Efficiency in the Soil Profile: The Role of Soil Acidity Alleviation, Nitrogen, and Phosphorus Availability - Bertolino, Karina Mendes [UNESP]; de Souza, Murilo [UNESP]; Jones, Davey L.; Rosolem, Ciro Antonio [UNESP] (MDPI, 2025)
Soil amendments such as limestone and gypsum can influence microbial carbon use efficiency (CUE) by altering nutrient stoichiometry, particularly nitrogen (N) and phosphorus (P). However, their effects beyond the topsoil, especially under no-till systems, remain unclear. This study assessed microbial CUE through substrate use efficiency (SUE) following glucose addition as a factor influencing carbon (C) sequestration potential. Two experiments were conducted in tropical soil. The first evaluated the addition of 14C-glucose (G) to soil treated with lime, lime + gypsum, and a control, with or without the addition of N. The second compared limestone + gypsum and control treatments, incorporating G with N and P. Soil microbial respiration (CO2 emission) was measured after 14 and 42 days. In the surface soil (0–10 cm), CUE increased with limestone or limestone + gypsum when N was applied. In the subsoil (40–60 cm), these amendments enhanced CUE compared to untreated soil in the absence of N. Treatments with G+N+P or G+P improved CUE in the surface soil. At the same time, G+N+P increased CUE in the subsoil regardless of acidity alleviation. Differences in 14CO2 evolution indicated higher microbial CUE with acidity correction. Balanced N and P applications significantly enhanced CUE, highlighting the importance of both soil acidity correction and nutrient availability for microbial carbon processing.